2009
DOI: 10.1007/s11079-009-9126-8
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Current Account Adjustment—Insights from Past Experience

Abstract: External imbalances, Current account adjustment, Cluster analysis, Multinomial logit, Expenditure switching, Expenditure reduction, F32, C14, C25,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 22 publications
4
31
0
Order By: Relevance
“…Compared with the international experience with current account reversals summarised above, it thus appears that the South African experience falls squarely in the “internal adjustment” category as identified by Algieri and Bracke (), i.e. most of the adjustment via declines in domestic demand (and thus imports) and very little from exchange rate adjustment (and thus exports) .…”
Section: South Africa's Experiencementioning
confidence: 95%
See 2 more Smart Citations
“…Compared with the international experience with current account reversals summarised above, it thus appears that the South African experience falls squarely in the “internal adjustment” category as identified by Algieri and Bracke (), i.e. most of the adjustment via declines in domestic demand (and thus imports) and very little from exchange rate adjustment (and thus exports) .…”
Section: South Africa's Experiencementioning
confidence: 95%
“…The IMF study quoted above, for example, reported on one subgroup with a median 3.5% GDP growth slowdown and a median 8% real exchange rate depreciation, and another with a median 0.75% increase in GDP growth and a median 18% depreciation. In a study that was explicitly designed to provide for this diversity in current account reversal experiences, Algieri and Bracke () used cluster analysis to identify different patterns of experience by countries. They identified three broad groups on the basis of their output and exchange rate experiences.…”
Section: International Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…Following Chinn and Wei (2013), we define three groups of exchange rate regimes: the fixed exchange rate regime corresponds to the first 4 categories of the fine grid in Reinhart and Rogoff (2004) and ranges from "no legal 6 A list of the countries in the sample is reported in 7 We used a linear interpolation method as part of which the last observation was matched to the source data. 8 As Algieri andBracke (2011) andIMF (2007) highlight, this criterion allows for a larger sample size compared to approaches that require the initial current account deficit to exceed a given magnitude. In a robustness check, we restrict the sample to reversals with an initial deficit larger than 2% of GDP as in Freund (2005) and find that our main results are qualitatively unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…9 As in Algieri and Bracke (2011), we use the country specific standard deviation rather than a fixed threshold in order to take account of country heterogeneity in current account dynamics. The highest current account standard deviation is in Norway (7.8%) while the lowest in France (1.2%)…”
Section: Introductionmentioning
confidence: 99%